Peran Guru Dalam Meningkatkan Pertumbuhan Iman Anak Sekolah Minggu - Selamet Samuel (KAPATA: Jurnal Teologi dan Pendidikan Kristen, 2025)
This research aims to examine the role of teachers in increasing the faith growth of Sunday School children. Using a literature study approach with qualitative methods, this research analyzes various literature sources related to the role of teachers in the context of children's religious education. The research results show that Sunday School teachers have a very crucial role in instilling religious values, building personal relationships with children, and creating a conducive learning environment. Effective teachers not only convey religious teaching material, but also become role models, facilitators and counselors for children. Apart from that, the use of creative and interesting learning methods can also increase children's interest and participation in Sunday School activities. In conclusion, the role of Sunday School teachers is very significant in the growth of children's faith. Therefore, efforts are needed to improve the quality and competence of Sunday School teachers so that they can carry out their role optimally.